EFFECT OF TOOL SHOULDER DIAMETER ON THE MECHANICAL PROPERTIES OF 1200 ALUMINUM FRICTION STIR SPOT WELDING (Journal of Engineering, 2011)
A friction stir spot welding (FSSW) process is an emerging solid state joining process in which the material that is being welded does not melt. In this investigation an attempt has been made to understand the effect of tool shoulder diameter on the mechanical properties of the joint. For this purpose four welding tools diameter (10,13, 16 and 19) mm at constant preheating time and plunging time were used to carryout welding process. Effect of tool diameter on mechanical properties of welded joints was investigated using shear stress test and Microhardness of joint which welded was studied. Based on the stir welding experiments conducted in this study the results show that aluminum alloy (1200) can be welded using (FSSW) process with maximum welding efficiency (80%) shear strength using tool diameter(19mm) with rotation speed (900rpm).